The role of potassium in muscle membrane dysfunction in end-stage renal disease. Issue 12 (December 2021) - Larsen, Lotte Hardbo; Z'Graggen, Werner J.; Bostock, Hugh; Tan, S. Veronica; Buus, Niels Henrik; Tankisi, Hatice
Highlights: Eighteen patients with end-stage renal disease were examined by blood samples and muscle excitability testing before and after hemodialysis. Muscle velocity recovery cycles and frequency ramp recordings were strongly associated with potassium levels, showing depolarization before hemodialysis and normalization after. Potassium-induced depolarization may be a major cause of muscle fatigue and weakness in end-stage renal disease patients. Abstract: Objective: Uremic myopathy is a condition seen in end-stage renal disease (ESRD), characterized by muscle weakness and muscle fatigue, in which the pathophysiology is uncertain. The aim of this study was to assess the role of abnormal serum constituents in ESRD patients by relating them to the excitability properties of the tibialis anterior muscle, at rest and during electrically induced muscle activation, by recording muscle velocity recovery cycles (MVRC) and frequency ramp responses. Methods: Eighteen ESRD patients undergoing hemodialysis were evaluated by blood sample, MVRC, and frequency ramp (before and near the end of dialysis treatment), quantitative electromyography, and nerve conduction studies. Patients were compared to 24 control subjects. Results: In patients, muscle relative refractory period, early supernormality, late supernormality after 5 conditioning stimuli, and latency of the last of 15 and 30 frequency ramp pulses were strongly associated with potassium levels (p < 0.01), showing depolarization before and normalization in the end of hemodialysis. Conclusions: In ESRD patients, the muscle membrane is depolarized, mainly due to hyperkalemia. Significance: Since normal muscle fatigue has been attributed to potassium-induced depolarization, it seems likely that this mechanism is also a major cause of the exaggerated muscle fatigue and weakness in ESRD patients.